Comparison of Donepezil, Memantine, Melatonin, and Liuwei Dihuang Decoction on Behavioral and Immune Endocrine Responses of Aged Senescence-Accelerated Mouse Resistant 1 Mice - Ju Zeng; Ju Zeng; Xiaorui Zhang; Xiaorui Zhang; Jianhui Wang; Jianhui Wang; Xiaorui Cheng; Xiaorui Cheng; Yongxiang Zhang; Yongxiang Zhang; Wenxia Zhou; Wenxia Zhou (Frontiers Media S.A., 2020)
Aging is a natural biological process associated with cognitive decline and neuroendocrine-immune system changes; the neuroendocrine-immune system plays crucial role in brain aging and neurodegeneration, and it is essential to discern beneficial attempts to delay the aging progress based on immunological aging. In this study, we have investigated the effects of Traditional Chinese Medicine (TCM)-Liuwei Dihuang decoction (LW)-and donepezil, memantine, and melatonin on cognitive decline in aging mice. The aged SAMR1 mice received oral administration of donepezil (1mg/kg), memantine (10 mg/kg), melatonin (10 mg/kg), and LW (10 g/kg) for 3 months. A shuttle box, Morris water maze, and elevated-zero maze were performed to assess cognitive function, and flowcytometry, Luminex, and radioimmunoassay were performed to measure the lymphocyte subsets, inflammatory factors, and hormones. We observed that survival days of mice was increased with melatonin and LW, the anxiety behavior was significantly improved by memantine, melatonin, and LW treatment, active avoidance responses significantly improved by LW, donepezil, and memantine, the spatial learning ability was significantly improved by donepezil, and LW and melatonin were beneficial to the spatial memory of old mice. For immune function, LW increased CD4+ and CD4+CD28+ cells and reduced TNF-α, IL-1β, and G-CSF in plasma, and it also promoted the secretion of anti-inflammatory factors IL-4, IL-5, and IL-10 by regulating the active of Th2 cells in spleen. Donepezil and memantine exerted protective effects against CD4+CD28+ cell decrease caused by aging and reduced the pro-inflammatory factors TNF-α, IL-1β, and G-CSF in plasma. Melatonin could reverse CD8+CD28+ cell imbalances and increased B cells. For endocrine factors, LW increased TSH levels in the pituitary, and melatonin increased the GH level in blood. Our findings indicated that LW improved the cognitive decline in aging mice, and this might be associated with modulation of the active T cells and HPG axis hormones as well as increasing anti-inflammatory factors. Meanwhile, donepezil and memantine have advantages in regulating adaptive immunity, melatonin has advantages in the regulation of B cells and pituitary hormones, and LW exhibits a better effect on neuroendocrine immune function compared with the others from a holistic point of view. LW might be a potential therapeutic strategy for anti-aging-related syndromes, and it can also provide a value on medication guidance about drug combinations or treatment in clinic.